Use of gas liquid chromatography/mass spectrometry for triazine herbicide residues analysis in forage and milk - Víden, I; Rathouská, Z; Davídek, J; Hajslová, J (Zeitschrift fur Lebensmittel-Untersuchung und -Forschung, 1987)
Residual s-triazines were isolated from forage and milk samples by methanol/chloroform extraction followed by column purification. The evaporated extracts were dissolved in acetone and analysed by gas chromatography with NPD detection and mass spectrometry. The detection limits for both methods were found to be about 5 approximately 10 ng of each s-triazine. The selective ions of the 10 s-triazines investigated (simazine, atrazine, propazine, terbuthylazine, cyanazine, desmetryne, ametryne, prometryne, terbutryne and methoprotryne) were chosen on the basis of an electron impact mass spectrometry study of the s-triazine standards and the whole mass spectra are given. Special attention was paid to the fragmentation of cyanazine and the general cleavage pathways of the s-triazines under investigation.
Keywords: Pesticide Residues; Animal Feed; Triazines; rezidua pesticidů; zvířata; spektrální analýza; triaziny; Chromatography, Gas; plynová chromatografie s hmotnostně spektrometrickou detekcí; Cattle; krmivo pro zvířata; Milk; skot; herbicidy; Spectrum Analysis; Herbicides; Animals; Gas Chromatography-Mass Spectrometry; chromatografie plynová; mléko